"Fidelity to the Mosaic Religion" in the book "Jerusalem, Or on religious power and Judaism" by Moses Mendelssohn: Translation, Presentation and Criticism - Abd AlRahman , Ibtehaj Radi (Dirasat: Shari’a and Law Sciences, 2020)
The book “Jerusalem, or on religious power and Judaism” published in English by Moses Mendelson is one of the most dangerous literature in the modern era that spoke about the Jewish enlightenment movement (Haskala) founded by the author, which led to World Zionism later. This research deals with the translation of a chapter of this book entitled "Fidelity to the Mosaic religion", a presentation and criticism, and illustrates the close connection between the Jewish Enlightenment movement and the movements of world Zionism, and the danger of this movement, which made the idea of the fabricated temple in Jerusalem is the core point of it. Hopefully, this research is a tool to the nation of the Holy Quran to know the size of the threat of its enemy. This study is based on translating texts from the book"Jerusalem, or the religious authority and the Jewish religion", then analyzing them, refuting and criticizing erroneous ideas such as the idea of canon law, the alleged structure and others, and responding to them from books of approved sources. The study reached several conclusions, including: Mendelssohn is a leading symbol of the Jewish Enlightenment Movement, which is called in Hebrew "haskala". The beholder finds that one of the most important resources of Mendelssohn’s culture is the Old Testament. We find that Mendelssohn follows a complex philosophical approach in presenting many issues.